Season-Aware Irrigation for Lowland Rice: Aquacrop-OSPy-Guided Rules to Enhance Water Utilization and Increase Dry Yields in Malang - Johan Ericka Wahyu Prakasa; Ajib Hanani; Shoffin Nahwa Utama (Akta Agrosia, 2026)
In monsoon climates, efficient irrigation for lowland rice requires adaptive strategies that respond to rainfall and soil moisture dynamics, rather than fixed schedules. This study utilized the AquaCrop-OSPy model, an open-source Python implementation of FAO AquaCrop v7.1 parameterized for paddy rice on clay-loam soil to compare two irrigation rules in Malang, Indonesia, over a decade (2015–2024) across three key planting periods: rainy season (January), transitional season (March), and dry season (June). The first schedule was a rain-aware basin top-up rule (0/10/50 mm based on 3–7-day rainfall) versus a moisture-threshold rule that triggers 50/10/0 mm when the root-zone depletion exceeds 70%, between 70–90%, or less than 90% of RAW. In the rainy and transitional plantings, the moisture-threshold rule reduced seasonal irrigation by 26% and 15% with no loss in yield (≤0.5% difference). During the dry-season planting, it increased yield by 11.4% with a moderate water trade-off (+21%). Consequently, water-use efficiency improved when rainfall contributed to crop demand, while targeted applications stabilized dry-season yields. These results show that simple, physiologically-based thresholds based on Aquacrop-OSPy’s paddy-rice parameters provide a feasible approach to year-round rice cultivation with more efficient water usage Keywords: Aquacrop-OSPy, fuzzy logic, internet of Things, irrigation scheduling, water-use efficiency